Phosphorus Recovery and Bioavailability from Chemical Extraction of Municipal Wastewater Treatment’s Waste Activated Sludge: A Case of Bangkok Metropolis, Thailand - Kay Thi Khaing; Chongchin Polprasert; Suwisa Mahasandana; Wanida Pimpeach; Withida Patthanaissaranukool; Supawadee Polprasert (Environment and Natural Resources Journal, 2022)
This study evaluated the extractability and bioavailability of Phosphorus (P) recovered from waste activated sludge (WAS) so as to reduce dependence on the import of non-renewable P resources. P extraction was carried out using sulfuric acid (H2SO4). A response surface methodology was used to optimize conditions for the chemical leaching of WAS. The results showed the optimum condition for leaching WAS with 0.1 mol/L H2SO4 for 30 min, resulting in 97% P released. The efficiency of P recovery by P precipitation was associated with pH value and Mg:P. At pH 7, 9, and 11, P recovery was 92, 92, and 91% with uncontrolled Mg and 93, 93, and 92% with sea salt (Mg:P, 2:1), respectively. However, the yield of the produced struvite was much lower compared with that of added sea salt. From elemental analysis, the yield of struvite precipitated at pH 9 of Mg:P, 2:1 was about 26%, and the total P content of the precipitate was 12%. Available P was almost 80% after 35 days of operation, which was higher than that of commercial fertilizers. Results of this study are expected to provide fully comprehensive information to decision-makers regarding the suitability of implementing P-composite matter recovered from WAS. This will also help close the loop of the P cycle for food cultivation in the human ecosystem.